1992
DOI: 10.7863/jum.1992.11.10.537
|View full text |Cite
|
Sign up to set email alerts
|

Doppler flow velocity waveforms in fetal surveillance of twins: a prospective longitudinal study

Abstract: In 37 consecutive twin pregnancies, monthly Doppler sonographic measurements were made of blood flow velocity waveforms of the internal carotid and umbilical artery of each fetus. A total of 197 Doppler studies were performed. Of the 74 infants, 23 were small for gestational age (SGA). Thirty-five of the SGA Doppler studies were abnormal, giving an overall sensitivity for predicting SGA fetus of 58% and a positive predictive value of 71%. These data are not as sensitive and specific as our earlier data; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Others [34] attributed the low PI values at the beginning and end of pregnancy to increased metabolic requirements and, therefore, lower cerebral vascular impedance to blood flow. Doppler flow studies in twins without growth retardation or discordance demonstrated changes throughout pregnancy similar to those in singletons [35] .…”
Section: Cerebral Arterial Doppler Waveforms In Normal Fetusesmentioning
confidence: 95%
See 1 more Smart Citation
“…Others [34] attributed the low PI values at the beginning and end of pregnancy to increased metabolic requirements and, therefore, lower cerebral vascular impedance to blood flow. Doppler flow studies in twins without growth retardation or discordance demonstrated changes throughout pregnancy similar to those in singletons [35] .…”
Section: Cerebral Arterial Doppler Waveforms In Normal Fetusesmentioning
confidence: 95%
“…A combination of systemic and cerebral Doppler parameters may complement real-time ultrasonography for the early diagnosis of abnormal growth in twin pregnancies [35] . Different trends in Doppler serial recordings were found according to the underlying mechanism of growth defect.…”
Section: Complicated Pregnancies and Deliveriesmentioning
confidence: 99%
“…Umbilical artery (UA) Doppler ultrasonography is an important tool in the assessment of high‐risk pregnancies, in particular singleton pregnancies affected by vasculopathy and growth restriction, but also in twin pregnancies affected by placental insufficiency. A meta‐analysis of randomized controlled trials of UA Doppler indices in high‐risk pregnancies showed that clinical actions guided by Doppler ultrasound reduced the odds of perinatal death by 38%.…”
Section: Introductionmentioning
confidence: 99%
“…63,64 As such, it has prognostic significance for the likelihood of growth restriction and perinatal morbidity and mortality, and it may change weekly if abnormal. 65 The values and patterns of change in vascular resistance are the same as for singletons. 66 Doppler assessment of umbilical venous blood flow and umbilical artery systolic/diastolic ratios are considered useful in predicting and confirming concordant and discordant growth in twins.…”
Section: Follow-up Ultrasound Examination and Antepartum Surveillancementioning
confidence: 99%